2014
DOI: 10.4239/wjd.v5.i2.224
|View full text |Cite
|
Sign up to set email alerts
|

Gas-forming liver abscess associated with rapid hemolysis in a diabetic patient

Abstract: We experienced a case of liver abscess due to Clostridium perfringens (CP ) complicated with massive hemolysis and rapid death in an adequately controlled type 2 diabetic patient. The patient died 6 h after his first visit to the hospital. CP was later detected in a blood culture. We searched for case reports of CP septicemia and found 124 cases. Fifty patients survived, and 74 died. Of the 30 patients with liver abscess, only 3 cases survived following treatment with emergency surgical drainage. For the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Since this disease is uncommon, but can be potentially life-threatening, our management probably prevented a rapid deterioration of the patient. We had no suspicion of a liver abscess, and the former therapy (ceftriaxone and levofloxacin) was empirical, but probably insufficient 5. We were only able to properly manage the infection when we noticed the gas-forming abscess.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since this disease is uncommon, but can be potentially life-threatening, our management probably prevented a rapid deterioration of the patient. We had no suspicion of a liver abscess, and the former therapy (ceftriaxone and levofloxacin) was empirical, but probably insufficient 5. We were only able to properly manage the infection when we noticed the gas-forming abscess.…”
Section: Discussionmentioning
confidence: 96%
“…Bacteraemia due to C. perfringens is uncommon, but often associated with a fatal outcome 1 4. Sepsis due to Clostridium infections is known to have a poor prognosis, often associated with shock and massive haemolysis 4 5. It is generally accepted that identifying the clinical features of C. perfringens infections is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…There were no statistically significant differences in gender between survivors and the deceased in patients with GFPLA-Cp. However, an earlier study found that significantly more female than male patients survived (P<0.05) [24]. The difference may be associated with basic patient conditions, such as the presence of underlying diseases, age, and nationality.…”
Section: Discussionmentioning
confidence: 89%
“…Another study from Japan reported that, among 5011 blood samples that were positive for any bacteria, only 41 were positive for Clostridium . Of the 41 samples, 16 were confirmed as septicemia, and 9 of the 16 were positive for C. perfringens [ 16 ]. The incidence of C. perfringens septicemia was reported to be 0.7 in 100000 per year in Canada [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course of C. perfringens septicemia and liver abscess is usually aggressive with high mortality ranging up to 70% to 100% [ 19 ]. The initial presentation can be variable, but fever and abdominal pain are common symptoms [ 16 ]. The abdominal pain has been strongly associated with a ruptured liver abscess.…”
Section: Discussionmentioning
confidence: 99%